Characterization and Antibacterial Mode of Action of Lactic Acid Bacterium Leuconostoc mesenteroides HJ69 from Kimchi. Issue 1 (13th June 2016) - Bajpai, Vivek K.; Rather, Irfan Ahmad; Majumder, Rajib; Alshammari, Fanar Hamad; Nam, Gyeong‐Jun; Park, Yong‐Ha
Abstract: This study characterized a lactic acid bacterium Leuconostoc mesenteroides HJ69 at biochemical and molecular level, isolate from traditional Korean fermented food Kimchi. Cell free supernatant (CFS) of L. mesenteroides HJ69 exhibited significant ( P  < 0.05) antibacterial effect as diameters of inhibition zones (14.34 ± 0.31 – 18.21 ± 0.23 mm) against the tested foodborne pathogenic bacteria with minimum inhibitory concentration and minimum bactericidal concentration values found in the range of 250–2, 000 and 500–2, 000 μg/mL, respectively. Further, CFS of L. mesenteroides HJ69 revealed its mode of action on membrane integrity as confirmed by the increased release of potassium ions (800 and 750 mM/L), loss of 260‐nm absorbing materials (3.85 and 3.77 OD), and increase in relative electrical conductivity (8.6 and 8.2%) against two selected bacteria L. monocytogenes KCTC‐3569 (Gram‐positive) and Escherichia coli O157:H7 (Gram‐negative), respectively. The above findings hypothesize that L. mesenteroides HJ69 compromised its mode of action on membrane integrity, suggesting its enormous potential in the food industry. Practical Applications: Asian countries have enormous use of fermented food products enriched with large populations of health‐beneficial lactic acid bacteria (LAB). This study describes the isolation of a LAB strain Leuconostoc mesenteroides HJ69 from traditional Korean fermented food Kimchi along with its biochemical and molecular characterization. The cell free supernatant of L. mesenteroides HJ69 displayed remarkable antibacterial effect against various foodborne pathogenic bacteria with a hypothesized mode of action in several assays. These findings suggest that L. mesenteroides HJ69 could be an effective candidate for its practical application in food industry to control the proliferation of foodborne pathogenic bacteria as a natural antimicrobial agent.